HMGB1 May Be a Biomarker for Predicting the Outcome in Patients with Polymyositis /Dermatomyositis with Interstitial Lung Disease. - Xiaoming Shu; Qinglin Peng; Xin Lu; Guochun Wang (PLoS ONE, 2016)
To investigate the significance of high mobility group box 1 (HMGB1) levels in polymyositis (PM) and dermatomyositis (DM) patients with interstitial lung disease and whether HMGB1 levels could predict disease outcome.HMGB1 levels were measured in sera from 34 patients with PM/DM and from 34 healthy controls by ELISA.Significantly higher serum levels of HMGB1 were found in patients with PM [12.75 ng/ml (4.34-25.07 ng/ml), p < 0.001] and DM [20.75 ng/ml (3.80-124.88 ng/ml), p < 0.001] than in healthy controls [5.64 ng/ml (2.71-8.71 ng/ml)]. Importantly, the average HMGB1 level in PM/DM patients with interstitial lung disease (ILD) was 25.84 ng/ml, which is significantly higher than that in PM/DM patients without ILD [12.68 ng/ml] (p < 0.05). A receiver operating characteristic (ROC) curve analysis revealed that the serum HMGB1 cutoff value that best discriminated PM/DM patients with ILD from those without ILD was 14.5ng/ml. The area under the curve was 0.87±0.05, and the 95% Confidence interval (CI) was 0.77-0.98. The diagnostic sensitivity and specificity of this serum HMGB1 cutoff level was 84.6% and 89% respectively. Patients with higher levels of HMGB1 expression had lower overall survival rates and disease-free survival rates, whereas patients with lower levels of HMGB1 expression had higher survival rates.Multivariate analysis showed that HMGB1 expression is a prognostic indicator for patient survival. These data support the notion that HMGB1 overexpression is involved in PM/DM progression for patients with ILD and is relative to its poor clinical outcomes.